Christian fundamentalism and the media in South India - Pradip N. Thomas
The turn towards Hindu nationalism in India has been a subject of academic study for over two decades. Events such as the pogroms (February-April 2002), against Muslims in Gujarat immediately after the Godhra killings in February 2002, the murder of the Australian-born evangelist Graham Staines (January 1999) and the destruction of the Babri Masjid (December 1992) received international and national media coverage